Correlations between canine allantoamniotic fluid and fetal development throughout the pregnancy term - Tantitaveewattana, Phakawat; Tiptanavattana, Narong; Ingkasri, Thitsana; Dermlim, Angkhana; Ampornpong, Thanawat; Uppathamchat, Artima; Jirayuwattanakun, Peruch (Frontiers in Veterinary Science, 2025)
Canine gestation typically lasts 63–65 days after the LH surge. Although ultrasonography is well established for monitoring fetal development in dogs, little is known about the dynamics of amniotic fluid. This study aimed to evaluate allantoamniotic fluid (AAF) using ultrasonographic examinations and correlate it with various factors of normal fetal development. Pregnant American Bulldogs underwent ultrasonographic examination (from weeks 3 to 8), and fetal parameters were collected weekly from 29 fetuses (n = 29). This study determined values for allantoamniotic fluid by cross-sectional view (AAFDC), allantoamniotic fluid by longitudinal view (AAFDL), biparietal diameter (BPD), cardio-thoracic ratio (CTR), abdominal cross-sectional area (ACA), gastric area (GA), and intercostal space (ICS). The correlation between fetal parameters and gestational age was analyzed. The AAFDC and AAFDL were first detected at week 3. Their maximum values, 34.60 ± 7.89 mm and 33.51 ± 9.59 mm, respectively, were observed at week 6 (p < 0.05). Subsequently, these values significantly and steadily declined from week 7 to the end (p < 0.05). In contrast, the BPD, ACA, GA, and ICS increased significantly from week 8 and were highly significantly correlated with gestation (p < 0.0001). Moreover, AAFDC and AAFDL showed a moderate correlation with day of gestation (DG) and day before parturition (DBP) (p < 0.0001). In conclusion, these findings propose the establishment of AAFDC and AAFDL as novel parameters for evaluating fetal wellbeing in canine practice.